Letter from Fritz Ullmann to Georg Bredig, July 1918 - Ullmann, Fritz (1918)
Fritz Ullmann (1875-1939), a German chemist and the editor of a technical encyclopedia of chemistry, thanks Georg Bredig (1868-1944) for writing an entry on catalysts. Ullmann additionally provides references and formatting information for intended revisions.
Keywords: Bredig, Georg, 1868-1944; Catalysts; Encyclopedias; Science publishing; Ullmann, Fritz, 1875-1939